(untitled) (Indian Journal of Arid Horticulture, 2025)
Intercropping under Kinnow based production system showed a significant effect on the growth of pre-bearing trees. The available nitrogen content during pre-bearing stage in leaves of Kinnow was found lower under all the intercrops and varietal combination thereof as compared to bearing trees and it increased progressively towards bearing of the tree. The intercrops did not show any significant effect on physico-chemical parameters of Kinnow fruits, whereas, the number of fruits/plant and fruit yield/plant was maximum under moong and minimum under cotton.